Role Of Ayurveda in Prevention of Communicable Diseases - Paudel, Pratima; Fiaz, Shamsa; Malashree , S G (International Research Journal of Ayurveda & Yoga, 2022)
Infectious or communicable diseases can be defined as an illness caused by another living agent, or its products, that can spread from one person to another, can cause emergency situation. Ayurveda has given practical explanation about the communicable diseases in various contexts which are applicable in day-to-day life in their prevention, and cure. The modes of transmission of the Communicable diseases, relative modes of prevention, and maintenance of health with Dinacharya & Ritucharya (daily practice & Seasonal practice) are well illustrated in classics. Various modes of transmission of the communicable diseases by Touch, Inhalation, Sharing Fomites, Polluted water, Air, Soil have been explained in Ayurveda along with the symptoms seen normally which follow cough, dyspnea, vomiting, rhinorrhoea, headache, fever etc. Infectious agents are plentiful, mutate rapidly, and can become resistant to drugs if not destroyed completely. Low vaccination rates, poor nutrition, age (young and elderly), and immunosuppression, Overcrowding, poor regional design and hygiene due to poverty, Polluted drinking water, rapid climate changes, and natural disasters, can lead to conditions that allow easier transmission of disease. The first and foremost aim of Ayurveda is Prevention of diseases and next is the cure of manifested diseases for which avoidance of the causative factors is the first line of management. There are minor diversions in the management of such infective conditions in Ayurveda such as Sadvritta (good conduct), Rasayana etc which can be effective method of prevention of communicable diseases.